Kedudukan Rahasia Dagang sebagai Harta Gono-Gini - Caesar Purwanto, Aldira Mara Ditta; Luthfiyah Chusnida, Nabilah (UNES Law Review, 2024)
Trade secrets or what is now known as undisclosed information are part of IPR which is parallel to other forms of IPR such as patents, brands, industrial product designs, copyrights, etc. The method used is normative juridical. According to legal experts, trade secrets are included in the category of intangible movable objects, in the form of rights that have moral, practical and economic value. Based on what is stated above, trade secrets become a right that has moral and economic value. However, when the owner of the IPR dies or there is a divorce in the household, it is very likely that problems will arise because of the economic value of the trade secret. The result is that trade secrets are intellectual property of high value and must be protected, then secrets can be said to be joint property if they are registered during the marriage period, but if they are registered before the marriage period they are said to be personal property of each individual. However, if the economic value is in the form of royalties on If the trade secret is received or obtained after the marriage, it is wealth in the household which becomes joint property. So, if a divorce occurs, it can become joint property that must be divided.